Lafaz Murādif dan Musytarak (Makna, Penerapan Dalam Nas dan Implikasi Hukum) - F, Faisal; Amin, Abd. Rauf Muhammad; F, Fatmawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study of murādif (synonyms) and musytarak (polysemy) in the texts is an important aspect in the study of Arabic, especially in understanding the Al-Qur’an and Hadith. This research aims to explore the meaning, application and legal implications of these two types of pronunciation. Murādif is used in the text to provide semantic variations that enrich the meaning and adapt the language style to a particular context, while musytarak is often a source of differences in interpretation due to its meaning depending on the context of its use. The application of murādif in the text aims to emphasize spiritual and legal messages. Meanwhile, the application of musytarak requires in-depth context analysis. The legal implications of this study show that a wrong understanding of murādif and musytarak can lead to differences in the interpretation of sharia law. This research contributes to the development of the science of interpretation and fiqh, especially in bridging differences in interpretation that arise due to variations in language meaning.